User Authentication Mechanisms for Remote Education Systems - Ekaterina Yurievna Gourina; Aleksey Albertovich Modestov (Безопасность информационных технологий, 2013)
Systems of remote education (RE) are now widespread. These systems are convenient in terms of simplicity, efficiency of education, costs, opportunities to study with a teacher when you are in different parts of the globe, to attend online lectures and seminars. The information circulating in this system is a source of making money for its owner, which of course does not want the system (and the information in it) to be used by not authorized users. In this article methods of authentication in such systems is discussed, because you can put a firewall, encrypt data transmissions, etc., but if there will be free access to the server, where all the information is held — it will all be useless.